Analysis of Investment Knowledge, Risk Perception and Motivation for Interest in Investing - Dewi April Yanti; Rita Dwi Putri; Lili Wahyuni (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This study aims to determine the influence of investment knowledge, risk perception, and investment motivation on students' interest in investing in the stock market. The research was conducted on all active students of the Accounting Study Program at the Faculty of Economics, Mahaputa Muhammad Yamin University, during the odd semester of the 2023/2024 academic year who have taken or are currently taking courses in the stock market and investment. This type of research is quantitative, and the sample was selected using the total sampling method, consisting of 118 students. The test results show that investment knowledge has a significant partial effect on students' interest in investing in the stock market. Risk perception also has a significant partial effect on students' interest in investing in the stock market. Investment motivation has a significant partial effect on students' interest in investing in the stock market. The results indicate that investment knowledge, risk perception, and investment motivation simultaneously influence students' interest in investing in the stock market.